Prognostic factors in medically inoperable early stage lung cancer patients treated with stereotactic ablative radiation therapy (SABR): Turkish Radiation Oncology Society Multicentric Study. (17th August 2020) - Sahin, Bilgehan; Atalar, Banu; Kaytan Saglam, Esra; Akgun, Zuleyha; Abacioglu, Ufuk; Arifoglu, Alptekin; Ozyar, Enis; Yaprak, Gokhan; Ozseker Isik, Naciye; Guney, Yıldız; Caglar, Hale Basak; Karaman, Sule; et al.
Abstract: Objective: We identified factors influencing outcomes in patients with medically inoperable early stage lung cancer (MIESLC) treated with stereotactic ablative radiation therapy (SABR) at 14 centers in Turkey. Materials and Methods: We retrospectively analyzed 431 patients with stage I‐II MIESLC treated with SABR from 2009 through 2017. Age; sex; performance score; imaging technique; tumor histology and size; disease stage radiation dose, fraction and biologically effective dose with an α/β ratio of 10 (BED10 ); tumor location and treatment center were evaluated for associations with overall survival (OS), local control (LC) and toxicity. Results: Median follow‐up time was 27 months (range 1‐115); median SABR dose was 54 Gy (range 30‐70) given in a median three fractions (range 1‐10); median BED10 was 151 Gy (range 48‐180). Tumors were peripheral in 285 patients (66.1%), central in 69 (16%) and <1 cm from mediastinal structures in 77 (17.9%). Response was evaluated with PET/CT in most cases at a median 3 months after SABR. Response rates were: 48% complete, 36.7% partial, 7.9% stable and 7.4% progression. LC rates were 97.1% at 1 year, 92.6% at 2 years and 91.2% at 3 years; corresponding OS rates were 92.6%, 80.6% and 72.7%. On multivariate analysis, BED10 > 100 Gy ( P  = .011), adenocarcinoma ( P  = .025) and complete response on first evaluation ( P  = .007) predicted favorable LC. BED10 > 120 Gy (hazard ratio [HR] 1.9, 95% confidence interval [CI] 1.1‐3.2, P  = .019) and tumor size (<2 cm HR 1.9, 95% CI 1.3‐3, P  = .003) predicted favorable OS. No grade 4‐5 acute side effects were observed; late effects were grade ≤3 pneumonitis (18 [4.2%]), chest wall pain (11 [2.5%]) and rib fracture (1 [0.2%]). Conclusion: SABR produced encouraging results, with satisfactory LC and OS and minimal toxicity. BED10 > 120 Gy was needed for better LC and OS for large, non‐adenocarcinoma tumors.